Banned drugs still on shelves – Who is responsible? - Waheed, Areeba (Journal of the Pakistan Medical Association, 2026)
I am writing to draw attention to a very concerning problem that endangers the public's health and safety: the continued sale of unprescribed drugs—including those banned by the Drug Regulatory Authority of Pakistan (DRAP)—by certain pharmacies. Recently, I witnessed it firsthand. Our mother was experiencing knee discomfort, so my brother went to a nearby pharmacy to get her a pain reliever. Surprisingly, the chemist gave out Diclofenac Potassium 75 mg —a medication that was banned by the Drug Regulatory Authority of Pakistan (DRAP) in its 317th meeting held on 16–17 May 2022.1 The drug was prohibited due to its known adverse effects, especially those related to cardiovascular and gastrointestinal health. This incident was alarming. There are significant concerns regarding the application and enforcement of DRAP legislation if such drugs, which have been outlawed for public safety, are nonetheless readily accessible over the counter. It also suggests that pharmacies that flout national regulations and public health obligations are subtly encouraging a risky self-medication culture. According to recent reports, the prevalence of self-medication in Pakistan ranges from 53% to 61.3%.2,3 The sale of these medications without a prescription carries significant health risks, such as an increased likelihood of drug abuse, adverse side effects, and chronic complications. It is not only a regulatory failing when prohibited medications are found in retail pharmacies; it is a life-threatening situation. I urge DRAP and health authorities to take swift and decisive action. To inform the people about the risks of consuming illegal and nonprescription drugs, there should be surprise inspections, fines for infractions, and public awareness programmes. Let us not wait for a tragedy to act. Strong regulatory enforcement and ethical pharmaceutical practices are essential for a safer and healthier Pakistan.